The Concept Of Just War and The Legality of War of Aggression Are Inextricably Linked With International Humanitarian Law - Aip Piansah (Zona Law And Public Administration Indonesia, 2023)
The attacks on New York and Washington on September 11, 2001 and the subsequent "war on terrorism" suddenly brought international humanitarian law into the limelight and once again highlighted the relationship between the causes of conflict on the one hand and respect for rules on hostile behavior and the protection of victims of war on the other. This article traces the history of rules restricting violence and prohibiting recourse to war. Despite the general prohibition of war in the Charter of the United Nations, the application of jus in bello remains independent of the causes of war, even in the fight against aggression, and any discriminatory application of international humanitarian law must be rejected. There are cavalier reasons to defend the principle of warrior arrogance by submitting to the laws of war. Whatever the moral and legal intent, the theory of discriminatory application of the laws and customs of war leads to an unacceptable result, namely unlimited war, because of the conception that war of aggression is not covered by international humanitarian law. State practice and the Rome Statute of the International Criminal Court, which entered into force on July 1, 2002, confirm the strict separation between jus in bello and jus ad bellum